Spatial-Temporal Evolution of Extensional Faulting and Fluid Circulation in the Amatrice Basin (Central Apennines, Italy) During the Pleistocene - Vignaroli, Gianluca; Mancini, Marco; Brilli, Mauro; Bucci, Francesco; Cardinali, Mauro; Giustini, Francesca; Voltaggio, Mario; Yu, Tsai-Luen; Shen, Chuan-Chou (Frontiers in Earth Science, 2020)
In extensional continental settings, crustal-scale normal faults can accommodate deformation and subsidence at their hanging wall via activation and deactivation of subsidiary tectonic structures. Geological data obtained from subsidiary structures are required to infer the position of the tectonic deformation during the spatial-temporal evolution of the growth-fault system, with significant implications for structures belonging to seismogenic settings. Here, we describe a subsidiary tectonic structure (the Amatrice Fault System) accommodating Quaternary extensional deformation in the Amatrice Basin (central Apennines, Italy), which is an intermountain morpho‐structural depression involved by the 2016–2017 seismic sequence. Structurally, the Amatrice Fault System defines a ~10 km-long tectonic feature running through the Amatrice Basin, and consists of NNW-SSE-striking and E-W-striking fault segments that interact and link over time. Cross-cutting fault relationships are used to reconstruct a kinematic scenario of fault growth and propagation under an ENE-WSW-directed crustal stretching, consistent with the paleostress regime governing the Quaternary activity of the central Apennines. The analysis of stable carbon and oxygen isotopes on syn-kinematic carbonate mineralizations (calcite veins and calcite fibers on fault surfaces) indicates a meteoric water circulation during the development of the growing fault structure, characterized by variable contributions of organic carbon (soil CO2), and suggesting surface rupture and hydrodynamic interconnection with the vadose zone during faulting. Geochronological U-Th dating on the same mineralizations indicates Middle-Late Pleistocene ages for tectonic activity of the Amatrice Fault System, with the younger age being 108±10 ka. Our results shed light on the long-term tectonics in the Amatrice Basin, in which the Amatrice Fault System records fault growth, hydrodynamic regime and structural permeability network developed under possible coseismic conditions during the Pleistocene. Activation and deactivation of minor tectonic structures, such as the Amatrice Fault System, can provide insights on the localization of tectonic deformation at the hanging wall of a master fault, with implication on the releasing seismogenic potential in active tectonic domains similar to the central Apennines.